(untitled) (American Journal of Language, Literacy and Learning in STEM Education (2993-2769), 2025)
Bibhutibhushan Bandyopadhyay (1894-1950) stands as one of the most influential figures in modern Bengali literature, renowned for his profound humanism, environmental consciousness, and realistic portrayal of rural Bengal. This research examines Bandyopadhyay’s literary contributions, particularly his masterpiece "Pather Panchali" and its sequel "Aparajito," analyzing his unique narrative style, thematic concerns, and lasting impact on Bengali literature. Through comprehensive analysis of his major works, this study explores how Bandyopadhyay revolutionized Bengali fiction by introducing a deeply empathetic perspective on poverty, nature, and human resilience. His works transcend mere social documentation to become universal statements about the human condition, establishing him as a bridge between traditional Bengali literature and modernist sensibilities. The paper argues that Bandyopadhyay’s environmental consciousness, decades ahead of his time, combined with his humanistic approach to storytelling, positions him as not merely a regional writer but a significant voice in world literature.